SELECTIVE EXTRACTION OF GOLD (III) BY INERT ORGANIC SOLVENTS AND DETERMINATION OF ITS METHYLENE BLUE (MB) DIRECTLY IN THE ORGANIC PHASE - Otakuziyeva Vazira Usmanjonovna; Turabdzhanov Sadritdin Maxamatdinovich; Kedelbayev Bakhitjan Shilmirzaevich; Giyasov Anvar Sharipovich; Rahmanberdiev Gaffar; Ponamaryova Tatyana Vladimirovna; Rakhimova Latofat Sobirjonovna (Academic Scientific Journal of Chemistry, 2020)
A new highly selective, accelerated and simple extraction photometric method for determining gold with MB directly in the organic phase has been elaborated. The developed method is tested on the analysis of production solutions of hydrometallurgical plants, concentrates and rocks without separation of accompanying elements. The developed method of extraction-photometric determination of gold with MB is recommended for the analysis of industrial solutions, waste water, ores, concentrates, rocks and other materials complex in terms of chemical composition without separation of the accompanying elements directly in the organic phase.